DISTRIBUTION OF FEEDING GROUNDS AND CETACEANS IN THE SEA OF OKHOTSK (Raspredelenie Kormovykh Polei i Kitoobraznykh v Okhotskom More) - Sleptsov,M. M. (1970)
A relatively constant mixing of the cold Okhotsk and warm Pacific water types takes place in the Kurile area off the western coast of Kamchatka, in northwest, central and south parts of the sea, as well as off the east coast of Sakhlain. The development of phyto- and zooplankton and the concentration of cephalopods and fishes that live in schools are associated with these 'frontal' zones which constitute the major grazing grounds for whales. Periodic changes of the hydrological regime, caused by the warming and cooling of various areas, facilitate the distribution of grazing grounds. As a result, the formation of grazing grounds is delayed, their distribution changed and the biomass of zooplankton diversified. Regularities in the peaks and failures of zooplankton development have not yet been elucidated, and, therefore, it is impossible to forecast the prospects of whaling due to lack of appropriate data. (Author) Trans. of Akademiya Nauk SSSR. Institut Morfologii Zhivotnykh. Trudy, v34 p79-92 1961, by M. Slessers.